La otra visita: legitimidad interna y convulsión externa. Richard Milhous Nixon en Costa Rica (1955) - Cascante Segura, Carlos Humberto (Anuario de Historia de América Latina, 2025)
By studying documents produced by US and Costa Rican agencies, as well as newspapers from both countries during that time, this article explores the contextual factors that surrounded Richard M. Nixon's official visit to Costa Rica. The article determines the fundamental role of the US-Costa Rica relationship, not only for the Costa Rican government but also for the opposition within domestic politics. Additionally, this research exemplifies how Costa Rican actors aimed not only to adapt to US policy but also, utilizing the tools at their disposal, sought to modify it in their favor. This perspective highlights that the objectives of US authorities were not always achieved as intended, revealing the limitations of US influence when dealing with smaller actors in the region, such as Costa Rican political factions.
Keywords: Costa Rica; United States; Cold War; Small States; Figueres.